(untitled) (Open Academia: Journal of Scholarly Research, 2024)
The article reveals the socio-psychological features of the athlete’s activity, and the diversity of the sports activity, the strength of the athlete’s mental experiences, prompts sports psychologists to focus on the study of the characteristics of mental processes in extreme conditions and the manifestation of strength, speed, precision of movement and complex movements in this process. held.